A Study on the Communicative Competence of Indonesian Teachers at Bilingual Programs - Heny Hartono (Universitas Jambi, Magister Program of English Education Department, 2020)
Teaching with English as a medium of instruction can be challenging for teachers in non-English speaking countries including Indonesia. The use of English as the language of instruction has become a part of marketing strategies for private schools to get more students. Apart from the marketing issue, the quality of the teachers should be on the top priority. Are the teachers qualified to serve as teachers at bilingual programs? Teachers’ communicative competence should add the general teaching competences of in-service teachers at bilingual programs. Unfortunately, schools hardly assess teachers’ communicative competence. This study aimed to find out the level of in-service teachers’ communicative competence and the correlation among the level of communicative competence aspects. This sequential explanatory study involved 82 in-service teachers who taught in English. The results of this study reveal that the subjects of this study were found in safe zone. It indicates that teachers of English speaking programs under this study can perform their tasks adequately although they cannot be called competent yet. From the Spearman correlational analysis, it was found out that the coefficient correlation was above 0.76 indicating a very strong correlation between communicative competence and its aspects and strong positive correlations among the communicative competence aspects. The results of this study provide valuable input of teachers’ communicative competence which can be further followed up with suitable trainings to improve teacher’s English competence.